Mandibular anterior lingual recession: keratinized tissue grafting and minimally invasive harvesting (2021)
INTRODUCTION: The mandibular anterior lingual (MAL) keratinized tissue (KT) band is often insufficient in dimension: <2 mm height of which <1 mm is attached gingiva (AG). Its gingival phenotype is commonly characterized as thin (<1 mm) gingival thickness (GT) and having inadequate (<1 mm) AG width. When surgical treatment is indicated, prevention of significant apical displacement of the gingival margin and improvement of long-term gingival stability are enhanced by KT increase and phenotype modification in order to establish thick GT and adequate AG. The aim of this case report is to describe a bilaminar surgical approach, the modified coronally advanced flap (mCAF) and connective tissue graft with retained KT band (mCAF + CTGkt). It is an outcomes-driven surgical approach for KT increase and phenotype modification in order to predictably establish thick GT and adequate AG. The mCAF + CTGkt procedure is minimally invasive, predictable, well-tolerated and addresses both the unique features of MAL anatomy and normal oral functioning movement during the postoperative healing phase. CASE PRESENTATION: A 48-year-old female presented with chief complaint of MAL progressive gingival recession (GR). Attachment loss of 3-4 mm and lack of both KT and AG were documented. Primary treatment outcomes objectives were GR cessation, establish KT, increase GT and AG. A secondary outcome was decreasing GR. CONCLUSION: The mCAF + CTGkt procedure resulted in KT increase, phenotype modification to establish thick GT and adequate AG, and decreased GR. It addressed unique features of MAL anatomy. Postoperative healing outcomes were not negatively impacted by normal oral functioning.